OGOH-OGOH PARADE AS A TOURISM ATTRACTION - Made Ika Kusuma Dewi; Bagus Ade Tegar Prabawa (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Tourism is one of the driving forces of the economy and the largest contributor to foreign exchange in Indonesia which plays a very important role in providing the welfare of the community, especially those around tourism areas. Bali, with its beautiful traditions and religion, has always been an endless attraction for tourists, making the tourists who come amazed and enchanted. There are various types of Hindu religious holidays, one of which is Nyepi. Ogoh-ogoh is a work of sculpture in Balinese culture that depicts Bhuta Kala's personality. In the teachings of Hinduism, Bhuta Kala represents the power (Bhu) which means the universe and (Kala) which is immeasurable and undeniable. This research approach is qualitative research. According to qualitative research is an in-depth process that refers to a methodology for exploring human problems. The data analysis technique used by researchers is the SWOT Analysis Technique, which is a way of analyzing internal and external factors into strategic steps in optimizing a profitable business. The ogoh-ogoh parade attraction is presented on every road in Bali during the Pengerupukan holiday celebration. This attraction can only be enjoyed during the Nyepi holiday series. To increase tourist attraction, of course the tourist attractions developed in this ogoh-ogoh parade are ogoh-ogoh which can move when paraded, ogoh-ogoh with very good detail so that the visualization of the ogoh-ogoh is real. Keywords; Ogoh-ogoh parade, Tourism Attraction, Communication Pattern